Zakat and Its Many Meanings in the Qur’an - Zulni Hidayah Putri Lubis; Nafisah Rahmah Nasution; Agustiar (Hikami : Jurnal Ilmu Alquran dan Tafsir, 2025)
The Qur'an, as the main source of Islamic teachings, was revealed in Arabic, a language rich in linguistic diversity and semantic depth, so that every word used has multiple meanings and is contextual. One of the keywords that has a central position in the Qur'an is the word zakat. Until now, studies on zakat have mostly focused on fiqhiyah aspects and legal practices, while linguistic studies and textual interpretations of the word zakat in the Qur'an are still relatively limited. In fact, the use of the word zakat in various verses shows a diversity of meanings that are not singular, as well as a development of meaning in line with the context of revelation. This study aims to analyze the use of the word zakat in the Qur'an by tracing its linguistic form, the context of the verses, and its diversity of meanings. This study is a library based qualitative research. Primary data consists of verses from the Qur'an containing the word zakat and its derivatives, while secondary data comes from classical and contemporary tafsir books, as well as relevant scientific literature. Data analysis was conducted using the Qur'anic semantic approach developed by Toshihiko Izutsu to reveal the basic and relational meanings of the word zakat, as well as the maudhu'i (thematic) interpretation method to systematically examine the verses on zakat based on the Makkiyah and Madaniyah contexts. The results of the study show that the word zakat in the Qur'an has a dynamic and multidimensional meaning. In the Makkiyah verses, zakat emphasizes the purification of the soul and the formation of individual moral values. Meanwhile, in the Madaniyah verses, zakat develops into an institutional and normative socio-economic obligation. This finding confirms that zakat is a Qur'anic concept that encompasses spiritual, social, and moral dimensions in an integrated manner. This study is expected to enrich the semantic study of the Qur'an and provide a more comprehensive understanding of the concept of zakat from the perspective of the Qur'an.